Le Flaubert de Charles Du Bos - Jacques Neefs (Flaubert: Revue Critique et Génétique)
Charles Du Bos devoted an unflagging attention to Flaubert’s work (except for Bouvard et Pécuchet, which, apparently, according to him did not exist), to Madame Bovary and in particular L’Éducation sentimentale. The connection between his essay “Sur le milieu intérieur chez Flaubert”, written in 1921, and extracts from his Journal, from 1923 to 1937, the comparisons with Gogol, Thomas Hardy, Tolstoy, Baudelaire, and Henry James that run through the writings of Du Bos, allow us to follow what he terms “the spiritual experience” of a materiality encompassed in the conquest of the triple demand of the Beautiful, the Living, the Truth. Du Bos detects the power of Flaubert’s work in the “disproportion” of his style, and the power of absorption that forms the density of his prose, showing an extraordinary process of conversion. The obscure spiritual experience thus pursued is that of an absolute in art, the paradoxical experience of a “mystic who believes in nothing” (as Flaubert called himself), which the critic links to a questioning of his own conversion.